Analysis of the academic offerings in professional programs of sports management and administration in Latin America - Rodríguez Buitrago , Daniel Felipe (Revista Educación Física Chile, 2025)
The present work intends to analyze the academic offer both at the professional and postgraduate level around the careers of the administrative and managerial field related to the sports sector in the different university institutions of Latin America. Making use of different portals and databases specialized in educational matters, the pertinent data was collected regarding the academic offer of different programs to establish trends, positioning, fields of study, and main characteristics that make up administrative and managerial careers. An attraction for the sports sector. Subsequently, in the development of this document, it was sought to establish some of the possible causes that make this type of professional programs a new academic trend that turns out to be greater in South American countries.